Fabrication and characterization of ZnO nanorods/Pd-Au contacts - Giri P.; Vyas S.; Chakrabarti P. (My University, 2025)
Vertically aligned ZnO nanorods were grown with two-layer structure including a buffer layer of AZO (50 nm). ZnO nanorods were grown by RF Sputtering on AZO buffer layer pre-deposited by thermal evaporation method. The XRD results confirmed the polycrystalline nature of the sample. The average height of 618 nm and the diameter of 474 nm of ZnO nanorods were measured with the help of Scanning Electron Microscope. The optical bandgap of the sample estimated by Ellipsometric measurement is 3.35 eV. Au/Pd dots were deposited on the ZnO nano-dot structure by shadow mask technique. The current-voltage (I-V) characteristics reveal the rectifying behavior of the contact with rectification ratio and ideality factor of 2534 at ±5 V and 4.06 respectively. Copyright © 2016 by American Scientific Publishers All rights reserved.